Pro-cyclical mortality. Evidence from Norway - Venke Furre Haaland; Kjetil Telle (Statistics Norway, Research Department, 2013)
Using variation across geographical regions, a number of studies from the U.S. and other developed countries have found more deaths in economic upturns and less deaths in economic downturns. We use data from regions in Norway for 1977-2008 and find the same procyclical patterns. Using individual-level register data for the same population, we then look at differences in pro-cyclicality across subsamples that are expected to be affected differently by the business cycle. Mortality is most pro-cyclical for young men (18-24), but there are also some indications of more pro-cyclical mortality for subgroups, such as the disabled, who are already dependent on the health-care system. Furthermore, the data allow us to look at pro-cyclicality in measures of morbidity, and we find procyclicality in disability, obesity and traffic accidents in densely populated areas. Finally, we investigate pro-cyclical mortality across socioeconomic groups and find that mortality is more procyclical for the well educated than the less educated, but it is less pro-cyclical for those with high earnings and more wealth than those with low earnings and less wealth. Overall, the observed associations between mortality and macroeconomic conditions seem to stem from a myriad of diverging mechanisms.
Keywords: I10; E32; J6; 330; Mortality; Morbidity; Health; Recession; Unemployment; business cycle